Axisymmetric vibration for micropolar porous thermoelastic circular plate - Kumar, Rajneesh; Kaushal, Priyanka; Sharma, Ravinder (Zielona Góra: Uniwersytet Zielonogórski)
The present investigation is concerned with a two dimensional axisymmetric problem in a homogeneous isotropic micropolar porous thermoelastic circular plate by using the eigen value approach. The Laplace and Hankel transform are used to solve the problem. The expression of displacements, microrotation, volume fraction field, temperature distribution and stresses are obtained in the transformed domain subjected to thermomechanical sources. A computer algorithm is developed for numerical computations. To obtain the resulting quantities in a physical domain, a numerical inversion technique is used. The resulting quantities are depicted graphically for a specific model. Some special cases are also deduced.
Keywords: micropolar porous thermoelasticity; eigen value; Laplace and Hankel transforms; thermomechanical sources